ANALISIS MIKRO-LONGITUDINAL PEMEROLEHAN FONOLOGI PADA ANAK USIA 3 TAHUN: PERSPEKTIF PSIKOLINGUISTIK DAN IMPLIKASINYA BAGI BAHASA INDONESIA - Abdul Nahrul Hayat; Bernadeta Maharani Sitanggang; Dea Febrima; Dini Oktavia; Faren Fiorenza; Fuja Alya Syafitri; Indah Rhamadani; Ridha Hasnul Ulya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study focuses on mapping the dynamics of phonological acquisition in 3-year-old Indonesian children, employing a micro-longitudinal approach. A mixed-methods design was implemented, integrating intensive naturalistic observation over 1.5 months with an integrated analytical procedure. Spontaneous speech data were collected using the participant observation technique, then analyzed both quantitatively and qualitatively. Quantitative analysis involved tabulating the frequency of phonological processes and calculating the Mean Length of Utterance (MLU), while qualitative analysis was conducted descriptively-analytically based on psycholinguistic developmental principles. The research findings indicate a dominance of phonological substitution (39.5%) and deletion (26.3%) processes, with an achieved MLU of 1.63. Consistent articulatory patterns identified include the apheresis of initial nasal consonant /m/, labialization, liquid yotacism, and functional reduplication. These findings confirm that sound deviations during this developmental phase are systematic and adaptive, reflecting cognitive-motor compensatory strategies employed by children in constructing the target phonological system. Theoretically, these findings enrich the validity of the Natural Phonology framework and Usage-Based Theory within the Indonesian context. Practical implications include providing normative references for clinical speech diagnosis and promoting a linguistic parenting approach responsive to children's developmental stages. This research makes a significant contribution to understanding early childhood phonological development in Indonesia.